Phytochemical standardization, formulation and evaluation of oral hard gelatin capsules from Pinus eldarica bark extract - Sajad Esmaeili; Ladan Dayani; Azade Taheri; Behzad Zolfaghari (Mashhad University of Medical Sciences, 2021)
Objective:The extract of Pinus eldarica bark contains many polyphenolic compounds that were studied due to their high antioxidant, anti-inflammatory and anti-mutagenic effects. Therefore, the purpose of the present study was to conduct phytochemical standardization and develop hard gelatin capsules from the extract of P. eldarica bark. Materials and Methods:Extraction was carried out by maceration method at room temperature for 72 hr using ethanol 70% followed by freeze drying. Quantification and standardization tests were performed using Folin-Ciocalteu method. Then, nine formulations were prepared containing different amounts of stearic acid (1-3%) and corn starch (3%, 10%, and 25%). Each formulation was characterized by FTIR and pharmacopoeial tests such as drug content, disintegration time, flowability parameters and drug release percent. The optimized formulation underwent stability studies at 75±5% humidity and 40±2°C. Results:The total phenolic content of the extract in terms of gallic acid equivalent was 362.8±5.4 mg/g and the total procyanidin content in the extract was 174.386±2.5 mg/g. FTIR revealed no interaction between the components. The results presented that the best formulation of the capsules was achieved they contained 3% of stearic acid and 25% of corn starch. This formulation showed 91.69±0.33% of drug content, 9.36±0.02 min disintegration time and 83.02±0.81% release percent. Moreover, it showed good flowability. Stability studies on the optimized formulation displayed that the formulation was stable within 6 months in the accelerated condition. Conclusion: In conclusion, results of the present phytopharmaceutical evaluations confirmed this product as a promising herbal capsule formulation.